As pioneiras da Brigada Militar de Pelotas-RS - (:unkn) unknown (Universidade Federal do Pampa, 2021)
A history, a memory as constituents of an identity and of an understanding of whether or not another, namely, the insertion of women No. 4 BPM, born in the city of Pelotas, Rio Grande do Sul, Brazil, what is this work about . The Military Brigade has a long-lived history, of great courage and bravery. Initially it was constituted only by men, within the logic of force and maintenance of order, which would count as daring virility to the male gender. Submitting 150 years from its institutionalization to a woman, she was inserted in the police department, obeying the redemocratization in Brazil and attending to new demands from the company regarding how many years of work exerted by the police. Eis that arises in the emergency of a female subject, prescribed no legal discourse, who should occupy a house on the street. Women who serve as mission to humanize police forces, finally, they are daring to motherhood and care as another, understood as natural characteristics of women. These military police officers must mediate the relationship between the virile institution and the others - notably, children, adults and other women - contributing, in such a way, to the modernization of the South-Rio Grandense Military Brigade. By force of words, it expresses in autobiographies, it presents voices of the most varied intonations, and knowledge of women that reveal repertoires of singular memories, and, at the same time, are familiar to recent history. Or autobiographical material is not constituted as a true passive of verification, because as narratives of life history express the meanings attributed by the narrator to his costume, considering the circumstances, the representations and interpretations of his reality. A set of works of an admirable wealth of sources - oral and documentary -, through which it is possible to recall past experiences, embracing the present and contemplating the future. Or what is historical and memorable for the pioneers? As expectations in being a military police officer; work; income; family; to training not course of soldiers; or ostensive policing (intelligence and technique); or internal work in the corporation; maternity; getting sick; friendships; difficulties; supersedes; studies; double working day; difficult to be recognized as a military police officer; courage; determination; the relationships established in the house and in the streets; the personal transformations; reform (retirement); other life projects. Speak also on the dilemmas posed by its position in the face of those that we always understand this position as revolutionary. These women will break borders in practice: they will use weapons to show, work in spaces and hours previously assigned, subject to police officers. worked in various modalities, such as: transit, school, golfinho operation, carnival, futebol, ostensive police, procissões, cemeteries (holiday of the deceased), birthdays and new year festivals, religious festivals, traditionalists, cologne, parade with dates allusive to Independence of Brazil, Tiradentes, a day of a soldier and so many others. Work internally within the corporation in various specialized sections. Transcendental borders, reinventing both the militarized ethos of 4th BPM and its supposed femininity. This book constitutes, no doubt,a research tool of great use for all those who nurture interest or some form of curiosity about the history, memory and identity of pioneering women in the Military Brigade of Pelotas, RS, Brazil.
The pioneers of the Military Brigade of Pelotas-RS
Keywords: Ciência Militar; Administração Pública; Rio Grande do Sul. Brigada Militar - História; Mulheres Policiais; Mulheres; Pelotas (RS); Military Science; Public administration; CNPQ::CIENCIAS HUMANAS